2011
DOI: 10.1017/s1751731110001904
|View full text |Cite
|
Sign up to set email alerts
|

Performance, ruminal changes, behaviour and welfare of growing heifers fed a concentrate diet with or without barley straw

Abstract: Two experiments were conducted to ascertain the effects of feeding an all-concentrate diet to growing heifers on performance, ruminal fermentation, behaviour and welfare. In experiment 1, eight tethered rumen fistulated Holstein heifers (143 6 8.7 kg, initial BW) were used to study the effects of treatment on intake, ruminal changes and behaviour. In experiment 2, 48 Friesian female calves (initial BW 5 84.5 6 1.37 kg) were used to study the effects of treatment on performance, behaviour and welfare in feedlot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 37 publications
(38 reference statements)
1
17
0
Order By: Relevance
“…Haptoglobin and fibrinogen concentration did not differ in veal calves fed corn moderately contaminated with Fusarium mycotoxins demonstrating that the calves were tolerant to the levels of the toxin in the diet [207]. The serum Hp concentration was not altered by an allconcentrate diet [208]. Haptoglobin and M-SAA3 in milk were used in assessment of the effect of a dietary negative energy balance diet on S. uberis induced mastitis and showed that the lower energy balance diet used in the study had a minimal effect on immune function [209].…”
Section: 3mentioning
confidence: 85%
“…Haptoglobin and fibrinogen concentration did not differ in veal calves fed corn moderately contaminated with Fusarium mycotoxins demonstrating that the calves were tolerant to the levels of the toxin in the diet [207]. The serum Hp concentration was not altered by an allconcentrate diet [208]. Haptoglobin and M-SAA3 in milk were used in assessment of the effect of a dietary negative energy balance diet on S. uberis induced mastitis and showed that the lower energy balance diet used in the study had a minimal effect on immune function [209].…”
Section: 3mentioning
confidence: 85%
“…In such a system, the consumption of concentrate makes up >90% of the total ration (Faleiro et al, 2011). As a result, the profitability of the production system depends largely on reducing the fattening time.…”
Section: Introductionmentioning
confidence: 99%
“…Devant et al (2000) reported that the proportion of concentrate and barley straw consumed by crossbred heifers changed from 95% and 5% at 80 kg body weight (BW) to 92% and 8% at 230 kg BW. In other studies, when Friesian heifers were also offered concentrate and barley straw separately and on an ad libitum basis during the fattening period, the average proportion of concentrate and barley straw intake was 90% and 10%, respectively (Robles et al, 2007;González et al, 2008;Faleiro et al, 2011). In these feeding conditions, rumination and chewing activity is more limited than when roughage is consumed in 2 shavings, in groups of three heifers per pen.…”
Section: Introductionmentioning
confidence: 84%